WHERE DID INDONESIAN ONLINE MEDIA PIONEER STAND ON INTERNET SHUTDOWN ISSUE? - Safitri, Reza; Noviadhista, Ulwan Fakhri (Universitas Muhammadiyah Yogyakarta, 2020)
In the past few years, the number of countries that implement internet shutdown policy has increased. The Indonesian government has also adopted a similar way. During 2019, the government has slowed or blocked internet access for three times: in May related to protest of Presidential Election in Jakarta; in August related to riots in Papua and West Papua; and in September in Wamena which also related to riots. In fact, besides its beneficial aspects, internet shutdown policy can cost bad to many sectors, including online journalism. This study tried to uncover how Detik.com ? as one of the very few pioneers of online journalism in Indonesia ? framed news about internet shutdown phenomena in Papua during August 2019. In this constructivist paradigm research, researchers analyzed 34 news samples using framing models from Pan and Kosicki, then discussed the findings with Social Construction of Reality Theory proposed by Berger and Luckmann. Based on the framing analysis done, Detik.com actively shaped the perception of internet shutdown as a positively aimed government?s policy, although still willing to give contrary views in the imbalanced portion. It practices ?crab journalism? to keep contributing to society as a media company and adapting to the political situation at the same time.